Olivine Morphology and Fabric During Diffusion Creep: Pure Shear Experiments. Issue 5 (2nd May 2022) - Kim, N.; Ando, A.; Yabe, K.; Hiraga, T.
Abstract: We deformed aggregates of Fe‐free olivine +20 vol% diopside in pure shear to study olivine grain morphology and fabric during diffusion creep. Samples were each deformed to a strain of around 0.7 at different temperatures and experimental durations, which resulted in different grain sizes among the samples due to grain growth. The sample microstructures were observed from each of the three principal stress directions, which revealed various 3D grain morphologies among the samples. Samples with tabular grains displayed a crystallographic preferred orientation (CPO) in olivine, while samples with weakly anisotropic grains had uniform CPOs. The CPO patterns vary from AG‐type (i.e., a uniaxial [010] concentration in the direction of sample shortening) to A‐type (i.e [010] and [100] concentrations in the directions of sample shortening and stretching, respectively), with intermediate types being the most common. The transition from AG‐ to A‐type fabrics is accompanied by a change from oblate to prolate grain morphologies. We explain the direct correlation between the olivine morphology and fabrics based on preferential grain‐boundary sliding (GBS) at boundaries with fewer steps (ledges). Oblate morphologies with well‐developed grain boundaries oriented parallel to (010) provide easy GBS along (010) and [ h 0 l ] planes and directions, respectively, while relatively prolate morphologies with boundaries parallel to (010) that are elongated along [100] provide easy GBS along (010) and [100] planes and directions, respectively. Boundaries form parallel to a particular crystallographic plane through differential grain growth in the directions of the crystallographic axes. Such grain growth causes fabric transitions during diffusion creep. Plain Language Summary: We deformed aggregates of Fe‐free olivine +20 vol% diopside in pure shear to study olivine grain morphology and fabric during diffusion creep. Various 3D grain morphologies and fabrics were found among the samples deformed at different temperatures and durations. We found a direct correlation between the olivine morphology and fabric, which is explained based on preferential grain‐boundary sliding at grain boundaries parallel to low‐index crystallographic planes. Such boundaries form through differential grain growth along the crystallographic axes. We propose grain growth to be the cause of fabric transitions during diffusion creep. Key Points: Various olivine grain morphologies and fabrics were observed after deformation to similar strains in pure shear during diffusion creep Grain morphology and fabric types are strongly correlated Grain morphology changes during grain growth, which results in a fabric transition